The Effects of Repeated Testing, Simulated Malingering, and Traumatic Brain Injury on Visual Choice Reaction Time - Woods, David L.; Wyma, John M.; Yund, E. W.; Herron, Timothy J. (Frontiers in Human Neuroscience, 2015)
Choice reaction time (CRT), the time required to discriminate and respond appropriately to different stimuli, is a basic measure of attention and processing speed. Here, we describe the reliability and clinical sensitivity of a new CRT test that presents lateralized visual stimuli and adaptively adjusts stimulus onset asynchronies (SOAs) using a staircase procedure. Experiment 1 investigated the test-retest reliability in three test sessions at weekly intervals. Performance in the first test session was accurately predicted from age and computer-use regression functions obtained in a previously studied normative cohort. Central processing time (CentPT), the difference between the CRTs and simple reaction time latencies measured in a separate experiment, accounted for 55% of CRT latency and more than 50% of CRT latency variance. Performance improved significantly across the three test sessions. High intraclass correlation coefficients (ICCs) were seen for CRTs (0.90), CentPTs (0.87), and an omnibus performance measure (0.81) that combined CRT and minimal SOA (mSOA) z-scores. Experiment 2 investigated performance in the same participants when instructed to feign symptoms of traumatic brain injury (TBI): 87% produced abnormal omnibus z-scores. Simulated malingerers showed greater elevations in simple than choice reaction times, and hence reduced CentPTs. Latency-consistency z-scores, based on the difference between the CRTs obtained and those predicted from CentPT latencies, discriminated malingering participants from controls with high sensitivity and specificity. Experiment 3 investigated CRT test performance in military veterans who had suffered combat-related TBI and symptoms of post-traumatic stress disorder and revealed small but significant deficits in performance. The results indicate that the new CRT test shows high test-retest reliability, can assist in detecting participants performing with suboptimal effort, and is sensitive to the effects of TBI on the speed and accuracy of visual processing.